Orphan Care in China - Liu Meng; Zhu Kai (Social Work & Society, 2009)
Orphan care in China was once provided by the central government as a means of social control. The centralized welfare delivery guaranteed some of the poorest orphans to be protected by the government. Since the economic reform, the central government started to relinquish its control over social welfare delivery, new forms of orphan care were introduced into China, sharing the responsibilities and burdens for caring the orphans. Yet, many issues and problems exist in social delivery due to a lack of finances, professionals, and policy support. In this chapter, we will discuss the background of social welfare changes in China, as pertains to orphan care, focusing on the different types of orphans as a result of social issues, service delivery, barriers and solutions. It is claimed that during the reform, the burden of orphan care in China may not be reduced in the coming future, and we offer suggestions to cope with that.